Hepatic lobe torsion in 3 dromedary camels. (January 2021) - Ibrahim, Abdelazim; El-Ghareeb, Waleed Rizk; Aljazzar, Ahmed; Al-Hizab, Fahad A.; Porter, Brian F.
Hepatic lobe torsion is a rare condition in domestic animals. Clinical signs are variable, with some cases remaining subclinical and others resulting in death. Most cases are diagnosed either by laparotomy or during postmortem examination. During postmortem inspection of 670 slaughtered dromedary camels, hepatic lobe torsion of the quadrate lobe was detected in 3 adult female camels. Clinical signs had not been noted on antemortem veterinary inspection, and hepatic lobe torsion was likely an incidental finding. Histologically, the affected liver lobe exhibited severe hepatocellular loss with replacement by fibrous connective tissue. When investigating abdominal pain in camels, veterinarians should include hepatic lobe torsion in the list of differential diagnoses.